Lifestyle intervention during pregnancy in patients with gestational diabetes mellitus and the risk of neonatal hypoglycemia: A systematic review and meta-analysis - Wang, Ya-Hai; Zhou, Huan-Huan; Nie, Zhibin; Tan, Jingwang; Yang, Zicheng; Zou, Shengliang; Zhang, Zheng; Zou, Yu (Frontiers in Nutrition, 2022)
Objective Neonatal hypoglycemia is a severe adverse consequence of infants born to mothers with gestational diabetes mellitus (GDM), which can lead to neonatal mortality, permanent neurological consequences, and epilepsy. This systematic review and meta-analysis of randomized controlled trials (RCTs) was conducted to explore the effect of lifestyle intervention during pregnancy in women with GDM on the risk of neonatal hypoglycemia. Methods PubMed, Web of Science, Cochrane Library, CINAHL, and SPORTDiscus databases were searched by 1st April 2022. Data were pooled as the risk ratio (RR) with 95% CIs of neonatal hypoglycemia. Random-effects, subgroup analyses, meta-regression analysis, and leave-one-out analysis were conducted, involving 18 RCTs. Results Prenatal lifestyle intervention could significantly reduce the risk of neonatal hypoglycemia (RR: 0.73, 95% CI: 0.54–0.98, P = 0.037). Subgroup analysis further demonstrated that the reduced risk of neonatal hypoglycemia was observed only when subjects were younger than 30 years, initiated before the third trimester, and with dietary intervention. Meta-regression analysis revealed that the risk of neonatal hypoglycemia post lifestyle intervention was lower in mothers with lower fasting glucose levels at trial entry. Conclusion We found that prenatal lifestyle intervention in women with GDM significantly reduced the risk of neonatal hypoglycemia. Only lifestyle intervention before the third trimester of pregnancy, or dietary intervention only could effectively reduce the risk of neonatal hypoglycemia. Future studies are required to explore the best pattern of lifestyle intervention and to determine the proper diagnostic criteria of GDM in the first/second trimester of pregnancy. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/#myprospero, PROSPERO, identifier: CRD42021272985.